Violations of fundamental rights of children and adolescents through violence - Soares, Leticia Gramazio; Depaoli, Laís Bastos; Lentsck, Maicon Henrique; Soares, Larissa Gramazio; Birolim, Marcela Maria; Igarashi, Ieda Harumi (Rev Rene, 2018)
Objective: to describe the violations of the fundamental rights of children and adolescents through violence. Methods: cross-sectional study of notifications of violations collected from the Information System on Protection to Children and Adolescents. Descriptive and analytical analyses were carried out by means of Chi-square tests for associations. Results: among the notifications, 61.2% were related to family and community living; 18.3% to education, culture, sport and leisure; 11.5% to freedom, respect and dignity; 8.5% to life and health; and 0.5% to professionalization and protection at work. There were 541 notifications making reference to violence, which included: 47.5% of sexual nature; white girls, 6 to 12 years old, and students, as main victims; and family members as the main perpetrators. Gender, age and schooling were associated with sexual violence. Conclusion: the fundamental rights of children and adolescents have been violated in most cases by the occurrence of violence of sexual, psychological, and physical nature, and negligence.